Development of a plant reference material for composition of a cement raw mixture - A. N. Smagunova; I. S. Shirokolobova; V. A. Kozlov; E. N. Korzhova; O. S. Krivchenko; L. P. Shaulina; A. L. Finkelshtein (Стандартные образцы)
A plant reference material (RM) was developed, which was certified in the content of fluorine-ion (% wt) in the cement raw mixture (PRM - 1 CM). Its metrological characteristics were set on the basis of results ofpotentiometric, photometric and titrimetric methods of analysis. The substantiation of the need for RM is given to increase the accuracy of results when determining fluorine in materials of cement production. The conditions are defined to use X-ray fluorescence method for estimating the material homogeneity in developing similar RMs. The interpretation of the error in residual heterogeneity in the results of analysis of powder materials and calculations of a smallest mass of representative sample is given when analyzing of such materials.